Simple outage probability bound for two-way relay networks with joint antenna and relay selection over Nakagami-m fading channels - Erdogan, E.; Gucluoglu, T. (INST ENGINEERING TECHNOLOGY-IET, 2015)
The performance of a multiple-input multiple-output amplify-and-forward two-way relay network with joint antenna and relay selection is analysed over Nakagami-m fading channels. Both approximate and asymptotic system outage probability expressions are derived, and diversity and coding gains for an arbitrary number of antennas, relays and fading severity are presented. Finally, the analytical findings are verified by numerical examples.
Keywords: probability; relay networks (telecommunication); Nakagami channels; antenna arrays; MIMO communication; amplify and forward communication; numerical analysis; outage probability; antenna; Nakagami-m fading channel; multiple-input multiple-output amplify-and-forward TWRN; MIMO AF two-way relay network; relay selection analysis; OP expression; approximate asymptotic system outage probability expression; coding gain; diversity gain; PERFORMANCE; Engineering